On almost pseudo-conharmonically symmetric ricci-recurrent manifolds - (:unkn) unknown (Sciendo, 2017)
The object of the paper is to study almost pseudo-conharmonically symmetric Ricci-recurrent manifolds. Some geometric properties have been studied. We also study an almost pseudo-conharmonically symmetric Ricci-recurrent spacetime. We prove that such a spacetime with non-zero constant scalar curvature becomes a quasi-Einstein spacetime and we obtain Segre’characteristic of such a spacetime. Finally, we investigate the possibility of a fluid almost pseudo-conharmonically symmetric Ricci-recurrent spacetime to admit heat flux. © 2018, Universitatii Al.I.Cuza din Iasi. All rights reserved.
Keywords: Almost pseudo-conharmonically symmetric manifold; Einstein field equations; Quasi-Einstein manifold; Ricci-recurrent manifold; Segre’characteristic